CREATING AN ATMOSPHERE OF THE RUSSIAN LANGUAGE IN PRESCHOOL EDUCATION: PROBLEMS AND SOLUTIONS - Makhammatkulova Nadirakhan Dilshodjon kizi (Scholars Digest Publishing, 2023)
The purpose of this research is substantiation of the system of work on teaching the Russian language to Uzbek preschool children who speak their native language, and learn Russian in kindergarten in the process of teaching Russian as a non-native language. Teach children to communicate correctly in their native and Russian languages, to be able to think deeply and correctly express them. From the first years of his life, a child must with all his heart, with all his soul love his native land, his homeland, his national culture and respect the culture of the Russian people. During the research these methods are used: theoretical, comparative, sociological and pedagogical. The proposed system of work is aimed at the complex mastery of the types of speech activity (listening, speaking) in Russian by preschoolers in bilingualism and contributes to the solution of educational problems.
Keywords: Russian language, native language, teaching Russian as a non-native language, preschool education standards, Uzbek-Russian bilingualism, early bilingualism, language environment.